Contribution to Mobile-Enhanced English Language Pedagogy among Iranian L2 Learners - Saeed Khazaie; Gholam Zarei; Ali Jalilifar (Journal of English Language Teaching and Learning, 2013)
This study aimed at providing learners with an opportunity not only to bring together their core and disciplinary knowledge to acquire major skills of learning English as a foreign language (EFL), and the intellectual challenge of these issues at the interface of media, language and religion, but also help the materials generators to produce suitable types of content to be delivered through the medium of mobile technology. Therefore, it sought to examine the new way of teaching EFL in the form of correspondence with respect to Iranian learners' native culture and language. For the purposes of this study, English was the target language for 680 Iranian students with pre-intermediate level of language proficiency whose native languages were Persian, Arabic, Georgian, and Turkish. This study took as its point of departure the existence of important differences between the two learning materials (off the shelf vs. Islamic culture) types; thus, applying the Qur'ānic criteria of intelligence, knowledge and virtue parallel with the digital representation of common textbook materials, materials delivery was adapted to the cellphone screen to be accessed by learners' in 18 virtual sessions. Learners took part in two summative and 18 formative components included in the assessment design of this study. Also, they all answered a questionnaire which yielded information concerning their attitude towards the target language, and learning through the wireless technology. Learners' short texting correspondence as well as their performance in battery and their answers to items of questionnaires formed the reference for analyzing the results. The gains from English Islamic materials were outweighed by the effects of obtaining materials which involved more categorized cases.